Influence of T1 Slope on the Cervical Sagittal Balance in Degenerative Cervical Spine: An Analysis Using Kinematic MRI. Issue 3 (February 2016) - Weng, Chong; Wang, Justin; Tuchman, Alexander; Wang, Jian; Fu, Changfeng; Hsieh, Patrick C.; Buser, Zorica; Wang, Jeffrey C.
Abstract : Study Design: A retrospective kinematic magnetic resonance imaging (kMRI) study. Objective: To evaluate the utility of kMRI in determining the relationship between cervical sagittal balance and TI alignment. Summary of Background Data: Thoracic inlet parameters play an important role in cervical spine sagittal balance. However, most of the literature is based on lower resolution cervical X-rays or CT scans in the supine position. Methods: Cervical spine kMRI of 83 patients with degenerative cervical spine conditions (20–68 yr of age) was analyzed for: (1) cervical spine parameters: C2–C7 angle, C2–C7 sagittal vertical axis (SVA), cranial tilt, and cervical tilt; and (2) T1 parameters: thoracic inlet angle (TIA), T1 slope, and neck tilt (NT). Multiple logistic regression analysis and Pearson correlation coefficients were performed. Results: The mean TIA, T1 slope, and NT were 78.0, 33.2, and 44.8°, respectively. The mean C2–7 angle, SVA of C2–C7, cervical tilt, and cranial tilt were −15.4°, 22.0 mm, 18.1°, and 15.1°, respectively. The ratio of cervical:cranial tilt was maintained as 55:45%. A significant correlation was found between the C2–C7 angle and T1 slope ( r = 0.731), TIA and C2–C7 angle ( r = 0.406), cervical tilt with C2–C7 angle ( r = 0.671), T1 slope with TIA ( r = 0.429), TIA with neck tilt ( r = 0.733), TIA with cervical tilt ( r = 0.377), SVA C2–C7 with cervical tilt ( r = −0.480), SVA C2–C7 with cranial tilt ( r = 0.912), and C2–7 SVA with the ratio of cranial tilt to cervical tilt ( r = 0.694). Conclusion: An individual with a large T1 slope required large cervical lordosis to preserve physiologic sagittal balance of the cervical spine. Cranial tilt was the cervical parameter most strongly correlated with SVA C2–C7, and thus may be a good parameter to assess decompensation of cervical sagittal balance. Level of Evidence: 3